A Phase II Trial of Melphalan Based Reduced-Intensity Conditioning for Transplantation of T-Replete HLA-Haploidentical Peripheral Blood Stem Cells with Posttransplant Cyclophosphamide in Patients with Hematologic Malignancies. (23rd March 2021) - Solh, Melhem M.; Hinojosa, Gabriel; Laporte, Justin; Solomon, Scott R.; Morris, Lawrence E.; Zhang, Xu; Holland, H. Kent; Bashey, Asad
Abstract : T-replete haploidentical donor transplants using posttransplant cyclophosphamide (haplo) have greatly expanded donor availability and are increasingly utilized. Haplo were originally performed using truly nonmyeloablative conditioning and a bone marrow graft. We have also developed myeloablative conditioning and peripheral blood stem cell (PBSC) grafts for use with haplo. However, some patients may not tolerate myeloablative conditioning but may still benefit from a more dose-intensified preparative regimen to control malignancy and diminish graft rejection. To this end, we enrolled 25 patients on a prospective phase II trial utilizing a regimen of fludarabine 30 mg/m 2 /day × 5 days and Melphalan 140 mg/m 2 on day -1 (flu/Mel) followed by infusion of unmanipulated PBSC graft from a haploidentical donor. GVHD prophylaxis included cyclophosphamide 50 mg/kg/day on days 3 and 4, mycophenolate mofetil on day 35, and tacrolimus on day 180. Median age was 57 years (range from 35 to 68). Transplantation diagnosis included AML ( n  = 11), ALL ( n  = 4), MDS/MPD ( n  = 6), NHL/CLL ( n  = 3), and MM ( n  = 1). Using the refined Disease Risk Index (DRI), patients were low ( n  = 1), intermediate ( n  = 13), and high/very high ( n  = 11). 22 out of 25 patients engrafted with a median time to neutrophil and platelet engraftment of 18 days and 36 days, respectively. All engrafting patients achieved full peripheral blood T-lymphocyte and myeloid donor chimerism at day 30. The 180-day cumulative incidence for acute GVHD grades II–IV and III-IV was seen in 20% (95% CI 8%–37%) and 8% (95% CI 2%–22%), respectively. The 2-year cumulative incidence of chronic GVHD was 16% (95% CI 5%–33%) (moderate-severe 12% (95% CI 3%–27%)). After a median follow-up of 28.3 months, the estimated 2-year OS, DFS, NRM, and relapse were 56% (95%CI 33–74%), 44% (95%CI 23%–64%), 20% (95% CI 8%–37%), and 36% (95% CI 17%–55%), respectively. Among patients with high/very high risk DRI, 2-year OS was 53% compared to 69% for low/intermediate DRI. When compared with a contemporaneous cohort of patients at our center receiving haploidentical transplant with nonablative fludarabine, Cytoxan, and total body irradiation flu/Cy/TBI regimen, the outcomes were statistically similar to the 2-year OS at 56% vs. 63% p = 0.75 and DFS at 44% vs. 46% p = 0.65 .